Growth, psychomotor development and morbidity up to 3 years of age in children born after IVF - Koivurova, S.; Hartikainen, A.-L.; Sovio, U.; Gissler, M.; Hemminki, E.; Järvelin, M.-R. (Human Reproduction, 2003)
BACKGROUND: To examine the long‐term child outcome after IVF until the age of 3 years in Northern Finland, we conducted a population‐based cohort study. METHODS: First, a cohort of 299 IVF children born in 1990–1995 was compared with a cohort of 558 controls representing the general population in terms of a multiple birth rate of 1.2%, randomly chosen from the Finnish Medical Birth Register (FMBR) and matched for sex, year of birth, area of residence, parity, maternal age and social class (full sample analyses). Second, IVF singletons ( n = 150) were compared with singleton controls ( n = 280). Third, a plurality matched control cohort ( n = 100) for IVF twins ( n = 100) was randomly chosen, matched as above, from the FMBR and analysed separately. Infant mortality rate was compared with the national rate from the FMBR. RESULTS: Infant mortality in the IVF group was >2‐fold higher compared to the national rate in the general population. The risk (OR, 95% CI) of low weight and height, below the lowest quartile, at 1 year of age (1.6, 1.1–2.2; 1.6, 1.1–2.4) and 2 years of age (1.5, 1.1–2.4; 1.7, 1.2–2.5) was significantly higher in the IVF group when compared with the general population control group. No statistically significant differences were found in the psychomotor development between the cohorts. Cumulative incidence of different diseases up to 3 years of age was significantly higher among IVF children in the full sample and singleton analyses (OR, 95% CI: 2.3, 1.7–3.2; 2.1, 1.3–3.3 respectively) especially regarding respiratory diseases (3.5, 1.9–6.5; 3.1, 1.0–9.4) and diarrhoea (3.7, 2.2–6.2; 5.7, 2.6–12.7), but not in twin comparisons. CONCLUSIONS: The growth of IVF children was behind that of control children during the first 3 years of life, but their psychomotor development was similar. Their postnatal health was worse, probably reflecting the problems in the neonatal period.